Effectiveness of Central Bank Independence via Its Internal Characteristics (International Journal of Banking and Finance, 2011)
This study examines central bank independence in developing countries of Latin America and Asia as well as selected developed countries. Many countries around the world, both developed and developing, have accepted the idea of central bank independence over the last several decades, so central banks have autonomy. A majority of studies has examined primarily the impact of central bank independence on inflation as promoting the theoretical benefits of a more stable and prosperous macroeconomic environment. However, there is only now sufficient data to empirically determine whether these claims are true. This research attempts to answer why developing economies with an informal sector resort to inflationary measures to finance their activities; how does a government induce an agent to choose the formal economy. In the trade-off between inflation and reserve requirements, the optimal policy is maximum inflation and minimum reserve requirements as increasing the steady-state utility of an optimizing agent. Also agents prefer the informal economy if policy relies on a maximum reserve requirement.